PENGARUH STORYTELLING MENGGUNAKAN BONEKA TANGAN TERHADAP KETERAMPILAN MEMBACA PADA KELAS 1 SEKOLAH DASAR - Wibowo, Diva Karita Putri; Mubarok, M. Khusni; Rahmawati, Ery (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to understand the impact of storytelling activities utilizing hand puppets on the reading abilities of 1 grade students at SDN Pucang 2 Sidoarjo. The research employs a quantitative methodology, specifically a nonequivalent control group design. The subjects of this investigation are students from classes 1-A and 1-C at SDN Pucang 2, with the experimental are students from class (1- A) comprising 20 students and the control class (1-C) also consisting of 20 students. Media utilization was validates by two expert: a lecturer specialized in media and a material expert, who is the homeroom teacher. Data collection involved validation questionnaires, as well as pretests and posttests. The normality and homogeneity tests yailded values of ≤ 0.05, indicating both normality and homogenity. The simple linear regression analysis produced an f- count of 85.677 with a significance level of 0.000, which is less than or equal to 0.05, thus confirming the significance of the findings. In hypothesis testing, a significance value of ≤ 0.05 led to the rejection of H0, establishing that the use of hand puppet media positively influences reading skills. Student engagement averaged a score of 79.64, categorizing it as good. The findings of this study demonstrate the effect of hand puppet media on the reading skills of students in classes 1-A and 1-C.